The relative risk of stress, anxiety and depression in women after miscarriage, ectopic pregnancy and normal pregnancy: A cross-sectional study - Zahra Hoseini Haji; Maryam Aradmehr; Morvarid Irani; Mohamad Namazinia (Mashhad University of Medical Sciences, 2023)
Introduction: Despite the high prevalence of abortion and ectopic pregnancy, there are limited studies on psychological complications following early pregnancy loss, so the present study was conducted with aim to compare the relative risk of stress, anxiety and depression in women with a history of ectopic pregnancy and miscarriage and normal pregnancy. Methods: This cross-sectional study was conducted on 312 women referred to Torbat Heydarieh hospitals from September to February 2021. One and three months after the diagnosis of miscarriage and ectopic pregnancy and proof of viable pregnancy, the data of psychological outcomes was collected through Cohen's stress, Beck depression and Spielberg anxiety questionnaires in three groups. Data were analyzed using SPSS software (version 16) and one-way ANOVA and Chi-square tests. P<0.05 was considered statistically significant. Results: The number of participants in the ectopic pregnancy group was 97, in the miscarriage group was 104, and in the normal pregnancy group was 111. One month after the diagnosis of the type of pregnancy, the prevalence of psychological complications including stress (7.6%), anxiety (47.6%) and depression (29.2%) was higher in the case group. Psychological complications three months later were higher in the case group and were 24.4%, 41.5%, and 24.3%, respectively. The relative risk of stress 3.32 and anxiety 1.75 was higher in the ectopic pregnancy group compared to miscarriage group, and the relative risk of depression was 2.86 higher in the miscarriage group. Conclusion: Considering the greater psychological outcomes of early pregnancy loss compared to normal pregnancy, using effective medical and counseling measures is recommended in order to prevent the adverse effects of psychological distress.